Effects of Cruise Flight Conditions on Power and NOx Emissions for High Bypass Turbofan Engine - Aygun, Hakan (Springer Nature, 2024)
In this study, effects of cruise flight conditions on exhaust gas emissions regarding PW4000 engine are scrutinized. For this aim, parametric cycle equations are encoded by considering PW4000 input values. Also, cruise flight regime is selected Mach between 0.6 and 0.7 and altitude 10 and 11 km. Based on ICAO database for NOx emissions at LTO cycle, cruise NOx emissions are calculated by employing BFF2 and DLR methods. Furthermore, after fuel flow of PW4000 engine is computed from cycle equations at defined flight conditions, CO2 and H2O emissions are calculated from combustion equations. According to emission results, average NOx emission index (EINOx) decreases from 28 g/kg to 25 g/kg due to rising altitude, whereas NOx value per unit second decreases from 0.03 kg to 0.024 kg. It could be highlighted that quantifying EINOx without using mentioned methods leads to wrong calculations. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.
Keywords: Boeing Fuel Flow Method; Efficiency; Turbofan; NOx emission